Assessing Humoral and Cellular Immunity in a Rat Model of Staphylococcal Bacterial Pneumonia: Penilaian Imunitas Humoral dan Seluler pada Model Tikus Pneumonia Bakteri Staphylococcus - Majeed, Wasan Abdulateef; Kadhim, Ola Abdulkareem; Mahdi, Zainab Hussein (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Staphylococcus aureus pneumonia remains a major global health concern due to its virulence, biofilm formation, and rising methicillin-resistant strains, which complicate treatment. Specific Background: Understanding the interplay between humoral and cellular immunity is crucial for designing effective interventions, as both antibody-mediated and T-cell–mediated responses contribute to pathogen clearance. Knowledge Gap: While immune evasion strategies of S. aureus are documented, quantitative insights into the temporal dynamics of antibody production, T-cell proliferation, and cytokine release during infection are limited. Aims: This study aimed to evaluate the kinetics of humoral and cellular immune responses in a rat model of S. aureus pneumonia. Results: Infected rats exhibited significantly elevated IgM and IgG levels, with IgM peaking at day 14 and IgG progressively increasing. Splenocyte proliferation and cytokine production (IFN-γ, IL-4) were markedly enhanced, particularly at day 21, indicating strong Th1 and Th2 activation. Novelty: The study provides an integrated temporal profile of dual-arm immunity in experimental S. aureus pneumonia, demonstrating concurrent robust humoral and cellular activation. Implications: These findings highlight the necessity of targeting both antibody and T-cell responses in vaccine design, potentially guiding the development of immunotherapies for effective prevention and treatment of S. aureus pneumonia.Highlight : IgM peaked on day 14, while IgG continued to rise until the end of the study. Splenocyte proliferation indicated strong T cell activation. Th1 and Th2 responses worked together to eliminate S. aureus from the lungs. Keywords : Staphylococcus, Humoral, Cellular, Immunity, Rat Model